ISO/IEC 9126 Quality Model for Evaluation of Student Academic Portal - Edy Budiman; Masna Wati; Joan Angelina Widians; Novianti Puspitasari; Muhammad Firdaus; Faza Alameka (IAES Indonesia Section, 2018)
The papers discuss and evaluate the quality of student academic portal using ISO / IEC 9126 quality modeling approach. Quality factors are tested and analyzed are characteristics of Usability, Reliability, Efficiency, and Portability, this evaluation is very important, considering the number of users of the portal system so much and growing. one of the efforts to improve and optimize the performance of the academic information system management team. Evaluate the quality of the user perception approach 10 principles of usability heuristics and internal site performance testing or web server. The results of analysis and testing of 4 quality characteristics have issued several recommendations for improvement and optimization of the performance of student academic portals.